Hubungan Family Centered Care terhadap Tingkat Kecemasan pada Anak Prasekolah yang Mengalami Hospitalisasi di Ruang Cempaka RSU Negara - Ika Winda Hidayati; Dwi Prima Hanis K; Ni Luh Ade Kusuma Ernawati (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Hospitalization is a condition where the child must stay in the hospital both planned and emergency to undergo therapy and treatment until the return home. During the process, children and parents can experience events which according to some studies are indicated by experiences that are very traumatic and full of anxiety. Efforts that can be made for health workers, especially nurses to reduce the level of anxiety in children is through Family Centered Care. This study uses cross sectional design. The population in the study were preschoolers who experienced hospitalization in the Cempaka’s Room of the Negara General Hospital is 34 respondents. The research sample used purposive sampling technique. The analysis of this study used the Sprearman Rank test. This study found that Family Centered Care in the Cempaka Room of State Hospital was mostly of good value and the results of anxiety of most children experienced moderate anxiety. The results of the research analysis state p = 0.094 (p value >0.05). There is no correlation between Family Centered Care and the level of anxiety of preschoolers who have experienced hospitalization in the Cempaka Room of the State Hospital.